Winners and losers from COVID-19: Evidence from Google search data for Egypt - Abay, Kibrom A.; Ibrahim, Hosam (International Food Policy Research Institute, 2020)
Evolving pieces of evidence show that services are hardest hit by the COVID-19 pandemic, both globally and in Egypt. Employing Google search data, we examine the implications of COVID-19 on demand for various services in Egypt. • We find that demand for those services that require face-to-face interaction, including hotels and restaurants, air travel and tourism services, significantly dipped after Egypt detected the first COVID-19 case and more so after the Egyptian government introduced major restrictions and curfews. For instance, in the first two months of the outbreak of the pandemic, February and March, demand for hotel and restaurant services contracted by about 70 percent. • In contrast, demand for services that substitute or reduce personal interactions, such as information and communications technologies (ICT) and delivery services, have enjoyed a significant boost. Demand for ICT services tripled, while demand for delivery services doubled in the four months since the outbreak of the pandemic. • Intuitively, these results suggest that individuals and enterprises operating in these sectors are expected to experience heterogenous impacts and damages associated with the pandemic. Our results, along with other evolving evidence, reinforce that those services and sectors negatively affected by the outbreak and spread of COVID-19 deserve attention. • Finally, our analysis highlights the potential of near real-time "big data" to substitute and complement conventional data sources to estimate economic impacts and, hence, inform immediate and medium-term policy responses.